Stagnated Democracy: The Rise of Formal Democracy in the Wake of Oligarchy Rules and Weak Pro-Democracy Movements - Hiariej, Eric (Springer, 2022)
This chapter will discuss the latest developments in democracy in Indonesia. The aim is to outline the context of the politics of citizenship studied in this volume, as the ongoing democratisation process is the basis of, and in turn shaped by, various struggles for citizenship rights. This chapter argues that the widely praised and celebrated democracy in Indonesia is currently stagnated. Despite a relatively stable political transition, successful instalment of core democratic institutions, high economic growth, and increasing freedom and liberty, problems such as corruption and other power abuse, poor welfare provision, and violence against minorities are holding back the democratisation process. At the centre of this stagnation is a weak popular representation in which the general populace hardly make better use of democracy to pursue their interests. The democratisation process, realised through a combination of moderate elite pacts and developing core rules and regulations, has produced merely a formal democracy that benefits elite the most, has yet to significantly challenge the power of oligarchy, and lacks sufficient political capacity for civil and popular groups to overcome the problem of weak representation. In this regard, the politics of citizenship in Indonesia should be better understood and debated against the relatively successful rise of formal democracy, the continuing grip of oligarchy, and the poor capacity of civil society- and popular sector-based activists in promoting democracy. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.